Synthesis and characterization of D-2PA-Pd(II)@SBA-15 catalyst via ``click chemistry'': highly active catalyst for Suzuki coupling reactions - Pathak, Aruna; Singh, A. P. (Journal of Porous Materials, 2017)
Copper catalysed cycloaddition reaction between azide and terminal alkyne, called as ``click reaction'', was found to be modular approach for the synthesis of facile, highly efficient and recoverable D-2PA-Pd(II)@SBA-15 catalyst. In efforts to synthesize the catalyst, the cycloaddition reaction between azido-functionalized mesoporous SBA-15 and N,N-dimethyl-2-propynylamine (D-2PA) has been carried out, followed by the complexation with PdCl2. To analyze physiochemical properties of synthesized materials, various characterization techniques such as CHN elemental analysis, X-ray diffraction, solid state C-13 and Si-29 NMR spectra, FT-IR, XPS, SEM, TEM and N-2 sorption analysis, TGA and DTA, UV-Vis spectroscopy have been carried out. The synthesized catalyst, D-2PA-Pd(II)@SBA-15, exhibited excellent catalytic activities with good product yield and high TON towards Suzuki coupling reaction of various aryl halides with phenylboronic acid. The effect of solvent, base and temperature on coupling reactions has also been described. The developed protocol offers recyclability of catalyst for multiple (four) times without any appreciable loss in stability and catalytic reactivity.
Keywords: Click reaction; Cycloaddition; mesoporous materials; SBA-15; Suzuki coupling